Learning Survival Models with On-Line Simulation Activities in the Actuarial Science Degree - Fernandez-Morales, Antonio (International Journal of Emerging Technologies in Learning (iJET), 2011)
The aim of this paper is to describe an on-line survival laboratory designed to enhance teaching and learning in the Statistics courses of the Actuarial Science Degree of the Uni-versity of Málaga. The objective of the on-line survival lab is to help students through a guided program of simulation activities with the understanding of the most important statistical concepts of the stochastic modeling of human survival, from an Actuarial point of view. The graphical interactive simulator is implemented as Java applets for the web version, and as a Javascript animation for a lite iPhone/iPod touch version. Finally, the results of a survey carried out at the end of the course are discussed to have a preliminary assessment of the studentsâ?? satisfaction with the resources, and their perception about the usefulness for their learning process.